Genotypes and phenotypes heterogeneity in PIK3CA-related overgrowth spectrum and overlapping conditions: 150 novel patients and systematic review of 1007 patients with PIK3CA pathogenetic variants. Issue 2 (7th March 2022) - Mussa, Alessandro; Leoni, Chiara; Iacoviello, Matteo; Carli, Diana; Ranieri, Carlotta; Pantaleo, Antonino; Buonuomo, Paola Sabrina; Bagnulo, Rosanna; Ferrero, Giovanni Battista; Bartuli, Andrea; Melis, Daniela; Maitz, Silvia; et al.
Abstract : Background: Postzygotic activating PIK3CA variants cause several phenotypes within the PIK3CA -related overgrowth spectrum (PROS). Variant strength, mosaicism level, specific tissue involvement and overlapping disorders are responsible for disease heterogeneity. We explored these factors in 150 novel patients and in an expanded cohort of 1007 PIK3CA- mutated patients, analysing our new data with previous literature to give a comprehensive picture. Methods: We performed ultradeep targeted next-generation sequencing (NGS) on DNA from skin biopsy, buccal swab or blood using a panel including phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin pathway genes and GNAQ, GNA11, RASA1 and TEK . Additionally, 914 patients previously reported were systematically reviewed. Results: 93 of our 150 patients had PIK3CA pathogenetic variants. The merged PROS cohort showed that PIK3CA variants span thorough all gene domains, some were exclusively associated with specific PROS phenotypes: weakly activating variants were associated with central nervous system (CNS) involvement, and strongly activating variants with extra-CNS phenotypes. Among the 57 with a wild-type PIK3CA allele, 11 patients with overgrowth and vascular malformations overlapping PROS had variants in GNAQ, GNA11, RASA1 or TEK . Conclusion: We confirm that (1) molecular diagnostic yield increases when multiple tissues are tested and by enriching NGS panels with genes of overlapping 'vascular' phenotypes; (2) strongly activating PIK3CA variants are found in affected tissue, rarely in blood: conversely, weakly activating mutations more common in blood; (3) weakly activating variants correlate with CNS involvement, strong variants are more common in cases without; (4) patients with vascular malformations overlapping those of PROS can harbour variants in genes other than PIK3CA .